ChatGPT in a programming course: benefits and limitations - Bringula, Rex (Frontiers in Education, 2024)
This paper explores the potential use and limitations of ChatGPT in a programming course, specifically focusing on its evaluation in a Data Analytics course due to its broad applications. The study reveals that ChatGPT offers valuable assistance to teachers in creating class materials, facilitating teaching-learning activities, and designing assessments. Students also benefit from the technology, as it can generate R programming codes and serve as a learning companion. However, limitations were identified, including the generation of incorrect reference materials, the tendency to produce pattern-like content, and potential misuse. The paper encourages replication of the study in other courses to uncover additional strengths and limitations, contributing to the development of ethical guidelines for responsible utilization of this exciting technology.